Brief research report: Investigating neurodiversity acceptance in the college classroom: an exploratory study - Hotez, Emily; Rava, Julianna; Kuo, Alice A. (Frontiers in Education, 2023)
Higher education represents a potential opportunity to address autism stigma and, in turn, prevent the negative health consequences of stigma as autistic college students transition into adulthood. The purpose of the current study was to investigate the general college student body and describe their 1) level of autism acceptance based on the neurodiversity framework utilizing the Autism Attitude Acceptance Scale (AAAS); and 2) self-reported knowledge and interests about neurodiversity.The sample (n = 90, M age = 21.86, SD = 1.18) featured undergraduates enrolled in a large, diverse, public university in the U.S. Approximately 32% (n = 29) identified as neurodivergent, with 5 identifying as autistic. Separate groups of students completed the AAAS-administered via Qualtrics-in February and September of 2022. In addition, students were provided the opportunity to ask up to three questions each about neurodiversity. We utilized qualitative thematic coding to extract themes from the neurodiversity questions.We derived frequency and descriptive statistics for each item and the two AAAS subscales: 1) the General Acceptance (GA) subscale (Cronbach's alpha = 0.89); and 2) the Attitudes toward Treating Autistic Behavior (ATAB) subscale (Cronbach's alpha = 0.77). Responses reflected high general autism acceptance. Responses demonstrated greater variability, however, with respect to attitudes toward treating autistic behaviors. Qualitative findings revealed both a high degree of interest in the neurodiversity movement, as well as high variability in knowledge and familiarity with its tenets.This research can inform higher education's efforts to address and prevent stigma towards autistic and other neurodivergent students.